Patriarchal Relationships, Subordination and Glorification of Marriage: The Dilemma of Women across Generation in Living and interpreting Love - Naufaludin Ismail (Jurnal Perempuan, 2018)
This paper focuses on the experience of women across generation living and interpreting love as part of their lives. Their experiences in living an interpreting love will be seen in two points, their romantic relationship and marriage or family institution. Based on the data of six subjects of research with different backgrounds like age, marital status and sexual orientation, showed that they have different perspective on love and marriage or family institution compare to mainstream society. They assume and believe love or romantic relationship has close relation with patriarchal cultural values, like men’s domination, subordination and ownership if we agreed with mainstream society’s thought on love. They also believe that marriage is an institution where patriarchy’s cultural values is produced there and will disadvantage women if the marriage is not built on equal and just relation. These six subjects of research agree with grand feminism narrative that love supposed to be not always related with ownership, men’s domination and must be liberating women as an independence and autonomous person.